Recyclable Robust Plastic Scintillation Resin Achieving the Exceptional Separation and Detection of Technetium‐99 - Tonghuan Liu; Yichen Hu; Junqiang Yang; Kesheng Hu; Bei Qi; Yun Zhou; Juan Tong; Man Wang; Liang Huang; Keliang Shi; Xiaolin Hou (Advanced Science)
Abstract Rapid detection and absorption of 99TcO4⁻ contamination in the environment are critical due to its high radioactivity, long half‐life, and significant environmental mobility. Resins have been demonstrated effective bifunctional properties for both the detection and separation of 99TcO4⁻. However, the poor stability of these compounds limits their practical application. Here, a chemical grafting strategy is presented to synthesize ultra‐stable plastic scintillation resin, in which 4‐vinylpyridine and divinylbenzene are cross‐linked as matrix polymer to withstand extreme conditions and a fluorophore “shield” to convert beta radiation into detectable signals. As expected, the as‐obtained resin exhibits a high adsorption capacity of 549.2 mg g⁻¹ for 99TcO4⁻ with a rapid kinetic response of just 10 min as well as superior selectivity at 1000 times excess of interfering ions and full reusability. Moreover, it showed remarkable stability under 800 kGy, 3.0 mol L−1 HNO3 or 2.5 L solution continuous leaching, consistently maintaining high separation and detection efficiency after recycling 10 times. This strategy paves a new way to develop stable resin for the rapid capture and accurate measurement of 99TcO4⁻, which owns great potential for practical application.